ONLINE LEARNING SYSTEMS: CLASSIFICATION, COMPONENTS, SUCCESSFUL PROJECTS - Seidametova, Z.S.; Seytveliyeva, S.N.; Temnenko, V.A. (Journal of Information Technologies in Education (ITE), 2012)
The article examines some aspects of online learning environment. Specifically made two-dimensional classification systems online learning presented spatio-temporal variations of the key factors and attributes of environmental e-learning. The characteristic of the most popular online learning projects, taking advantage of cloud technologies, – Coursera and Udacity.